EFEKTIFITAS PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA TUNAGRAHITA RINGAN - Yani Prihati; Prita Paramita (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2016)
In SLB Pembina Yogyakarta, the process of science learning in class VII SMPLB Tunagrahita need to be improved. The media used in learning process can’t encourage the activity and enthusiasm of students. Those media just able to develop cognitive only. So it urgent to develop learning media that help learning process and make the students learn natural phenomena easily, and also be able to behave like scientist according to their ability. There are two indicators that address best result, those are the process and result success. Successful process is a condition where the students can participate the learning process actively with the help of that media. The result indicator is the increasing of KKM percentage. The result of this research showed that the using of learning media bases on computer can increase the students’s activity and participation, and also increase studen’s learning outcomein sscience. this fact was proved by the high percentag og students KKM for 20%. Keywords: Lectora, Science learning media, tunagrahita